Re-entrant spin glass transitions: new insights from acoustic absorption by domain walls. Issue 1 (December 2017) - Kustov, S.; Torrens-Serra, J.; Salje, E.; Beshers, D.
Abstract Re-entrant spin glass (RSG) transitions in Ni-Mn and Au-Fe have been reassessed by acoustic measurements of the magneto-mechanical damping by domain walls. Stress-induced non-thermally activated domain wall dynamics is progressively replaced by an intense thermally activated relaxational response when the temperature approaches the RSG freezing point. A "frozen" state with negligible motion of domain walls on atomic and mesoscopic scales occurs in the RSG. We propose that RSG freezing has its origin in intrinsic properties of domain walls.